The Revitalization of Islam in Southeast Asia: The Case of Darul Arqam and Jemaat Tabligh - Horstmann, Alexander (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2006)
Darul Arqam was founded relatively late in 7968 in Malaysia, while Jemaat Tabligh was founded 1927 in India, but is active in nearly all countries where Muslims live. Both organizations could be described as grassroots and have from the very beginning sought to revitalize Islam by emphasizing piety, da'wa, Islamic rituals and most of all, the establishment of a utopian commune. Thus this article, amongst other things, seeks to analyze the influence that these two movements have on their followers' lives and the integration of those followers into their respective utopian projects.DOI: 10.15408/sdi.v13i1.576